2010
DOI: 10.1016/j.juro.2009.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HYAL1 and Survivin RNA as Diagnostic Molecular Markers for Bladder Cancer

Abstract: The detection of urinary HYAL1 and survivin RNA is a promising noninvasive test for bladder cancer early detection. HYAL1 RNA was more sensitive and specific than urine cytology. Semiquantitative reverse transcriptase-polymerase chain reaction is favored for its high sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…[34] A study based on 278 Egyptian patients with bladder cancer showed that urinary survivin was positive 75.5% and 10.7% in malignant and benign cases respectively. [35] Chinese publishers recently published a paper on the role of survivin in the bladder cancer. [36] They found that none of the adjacent normal urothelial tissues to the cancerous bladder tissue had expressed survivin whilst 60% of bladder cancerous had expressed surviving.…”
Section: Resultsmentioning
confidence: 99%
“…[34] A study based on 278 Egyptian patients with bladder cancer showed that urinary survivin was positive 75.5% and 10.7% in malignant and benign cases respectively. [35] Chinese publishers recently published a paper on the role of survivin in the bladder cancer. [36] They found that none of the adjacent normal urothelial tissues to the cancerous bladder tissue had expressed survivin whilst 60% of bladder cancerous had expressed surviving.…”
Section: Resultsmentioning
confidence: 99%
“…One study revealed 100% FasL positive immunoreactivity in schistosomal BC and 0% in controls by indirect immunohistochemistry using avidin-biotin-peroxidase complex (ABC) method [55]. Other studies investigated the expression of urinary apoptosis inhibitory gene, survivin by ELISA or semiquantitative reverse transcriptase-polymerase chain reaction (RT-PCR) reporting 78.33% sensitivity and 82.5% specificity in BC and 72.2% sensitivity in schistosomal BC [56,57].…”
Section: Urine Markers Related To Apoptosismentioning
confidence: 99%
“…Quantitative enzyme immunoassay and PCR ELISA [51] 2-genetic urinary biomarkers related to apoptosis Fas (CD95) and FasL Indirect immunohistochemistry using avidin-biotin-peroxidase complex (ABC) method [55] Survivin ELISA or semiquantitative reverse transcriptase-polymerase chain reaction (RT-PCR) [56,57] TGF-b-1 Immunoelectronmicroscopic and immunocytochemical techniques [58] 3-epigenetic urinary biomarkers RSSF1A, RARb2, RUNX3, TIMP3, MGMT, p16 and ARF Quantitative methylation-specific PCR [60] RARb(2) and APC genes Methylation-specific PCR [61] miR-210, miR-10b, and miR-29c SYBR green-based PCR array [65] miR-96 QRT-PCR [66] B. Biomarkers related to angiogenesis…”
Section: -Genetic Urinary Biomarkers Related To Cell Cyclementioning
confidence: 99%
“…Recently, a number of studies demonstrated that HYAL-1 was a potential urinary marker for predicting progression to muscle invasion and recurrence of human bladder cancer. Eissa et al studied 166 patients diagnosed with bladder carcinoma, 112 with benign bladder lesions and 100 healthy volunteers who served as controls, using HYAL1 as a diagnostic molecular marker for bladder cancer (Eissa et al, 2010). They found that the positivity rates of HYAL1 RNA on qualitative reverse transcriptase-polymerase chain reaction were significantly different among the 3 groups.…”
Section: Hyal-1mentioning
confidence: 99%